Applying Plant Growth Promoting Rizobacteria (PGPR) of the Genus Pseudomonas ssp as Biological Controllers of Insects and Plague Nematodes - Canchignia Martínez, Fabricio (2015)
Rare an alternative that has proven not to generate resistance in pathogens. Pseudomonas strains play an important role in biocontrol, because they provide a great variety of bioactive compounds to control plant pathogens. The information search   focused on the study of Pseudomonas spp isolates which have the ability to diminish the viability of such pathogens as: fungi, bacteria, nematodes through the use of an antagonist mechanism inducing plant defense systems through systemic acquired resistance (SAR) and induced systemic resistance (ISR).